Social Economic Conditions of The Community and The Entrepreneurship of Sheep Manure as Organic Fertilizer On Corn Waste Production In Kisar Island - Melianus Ririmase, Pieter; Melkianus Puttileihalat, Paulus; W. Patty, Christian (Devotion : Journal of Research and Community Service, 2022)
The agricultural sector in Indonesia is famous for its abundant natural products and soil fertility. The agricultural sector provides the largest contribution as a supporter of food security. The socio-economic condition of the community is one of the determining factors in supporting the agricultural sector. Sheep is one of the potential animal natural resources cultivated by the people on Kisar Island. Breeders are expected to always be able to improve their knowledge in carrying out various business activities, especially in utilizing the production of sheep dung to be used as organic fertilizer for plants. The purpose of this study was to determine the socioeconomic conditions of farmers, to determine the production of maize using sheep dung, to determine the relationship between the use of sheep dung and maize production on Kisar Island, and to determine the relationship between maize waste feed consumption and sheep productivity on Kisar Island. The results showed that sheep farmers on Kisar Island had low bargaining power, limited capital, and information, but the social conditions of the community in a participatory manner were very good in livestock business activities in the area. Sheep farmers on Kisar Island are always in a low bargaining position in marketing their products, due to capital constraints, long distances from marketing locations, lack of accurate information and pressure on family needs. corn production of 2.98 tons/ha/year. The relationship between the utilization of manure and production shows a non-significant relationship (P>0.05) where the use of sheep manure has not contributed significantly to the growth and production of maize, Consumption of corn waste feed with sheep productivity on Kisar Island showed a very significant relationship (P < 0.01) with the contribution of straw waste feed consumption to sheep productivity of 83.70%.